Basaloid Squamous Cell Carcinoma of the Oral Cavity: A Report of Two Cases with Review of Literature - Sudarvizhi Thiruvasagam; Shalinipriya Nesamani; Varsha Upadya; Soniya Adyanthaya; Maji Jose (Journal of Clinical and Diagnostic Research)
Basaloid Squamous Cell Carcinoma (BSCC) is a rare, aggressive variant of squamous cell carcinoma. It exhibits diverse histological features. The present case reports provide valuable insights by focusing on BSCCs of the tongue and gingiva, including a detailed review of 19 cases in the literature specific to gingival involvement, which is a less common location for BSCC. Case 1 involves a 76-year-old female with a history of BSCC who presented with a painful 4x4 cm recurrent lesion on her upper lip. Case 2 is a 62-year-old male smoker with a history of thyroid carcinoma who exhibited a rapidly growing, painful 2x2 cm lobulated mass on his tongue. In both cases, a thorough clinical evaluation and incisional biopsy were performed to establish a diagnosis. Histopathological examination confirmed BSCC and both lesions were surgically excised with wide margins, taking their age into consideration. Both patients have since remained recurrence-free under regular follow-up, emphasising the efficacy of timely intervention. The present study findings suggest that while radiation exposure may contribute to the development of BSCC of the tongue, it is not the only causative factor. Other factors, such as smoking or genetic predispositions, may also play a role. The aggressive nature of BSCC, particularly in the gingiva, highlights the need for a comprehensive diagnostic approach, including biopsy and histopathological evaluation. Furthermore, the present cases align with evidence suggesting that combining surgery with postoperative chemotherapy or radiation therapy may not significantly improve survival outcomes. Long-term follow-up remains important to monitor for any potential complications.